2006
DOI: 10.1038/nature05194
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the p53 pathway in retinoblastoma

Abstract: Most human tumours have genetic mutations in their Rb and p53 pathways, but retinoblastoma is thought to be an exception. Studies suggest that retinoblastomas, which initiate with mutations in the gene retinoblastoma 1 (RB1), bypass the p53 pathway because they arise from intrinsically death-resistant cells during retinal development. In contrast to this prevailing theory, here we show that the tumour surveillance pathway mediated by Arf, MDM2, MDMX and p53 is activated after loss of RB1 during retinogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
632
3
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 538 publications
(671 citation statements)
references
References 32 publications
31
632
3
5
Order By: Relevance
“…Therefore, despite strong similarities between the p53-binding domains of Mdm4 and Mdm2, minor differences are sufficient to reduce the inhibitory effect of Nutlin-3 on Mdm4-p53 binding. Consistently, some studies have suggested that Mdm4 levels determine the sensitivity of tumor cells for anticancer therapy (Hu et al, 2006;Laurie et al, 2006;Patton et al, 2006;Wade et al, 2006).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Therefore, despite strong similarities between the p53-binding domains of Mdm4 and Mdm2, minor differences are sufficient to reduce the inhibitory effect of Nutlin-3 on Mdm4-p53 binding. Consistently, some studies have suggested that Mdm4 levels determine the sensitivity of tumor cells for anticancer therapy (Hu et al, 2006;Laurie et al, 2006;Patton et al, 2006;Wade et al, 2006).…”
Section: Introductionmentioning
confidence: 64%
“…In addition, it has been reported that Mdm4 can enhance Mdm2-mediated ubiquitination and degradation of p53 (Stad et al, 2000. Similar to Mdm2, Mdm4 has been found overexpressed in a significant number of various human tumors and tumor cell lines, in general correlating with the expression of wild-type p53, suggesting that Mdm4 contributes to p53 inactivation during tumorigenesis (Riemenschneider et al, 1999(Riemenschneider et al, , 2003Ramos et al, 2001;Danovi et al, 2004;Laurie et al, 2006). As both Mdm2 and Mdm4 are overexpressed in many tumors that retain wild-type p53, they are attractive targets for the development of anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Un autre acteur majeur de cette voie de régulation est MDM4 (aussi connu sous le nom de MDMX). MDM4 est un inhibiteur spéci-fique de p53 qui est amplifié ou surexprimé dans 10 à 20 % des cancers [1], et jusqu'à 65 % des cas de rétinoblasto-mes [7]. MDM4 partage des similitudes structurales avec MDM2.…”
Section: Réactivation De P53 Dans Les Tumeursunclassified
“…Cependant, il ne contrôle pas la stabilité de p53, mais son activité transcriptionnelle [8,9] (Figure 1 [1,7] (Figure 1). La recherche d'antagonistes de MDM4 plus efficaces est un objectif clinique important, puisque l'inhibition spécifique de MDM4 dans les cellules tumorales limite la croissance des tumeurs xénogreffées [7,8] Certaines données suggéraient une sensibilité accrue des cellules tumorales à la Nutlin du fait d'une altération de leur transcriptome [11], mais d'autres montraient que l'inactivation totale de MDM2 dans des cellules normales est rapidement létale chez la souris [12]. Trois nouveaux modèles murins apportent maintenant des informations cruciales sur ces points et révèlent également des informations inattendues.…”
Section: Réactivation De P53 Dans Les Tumeursunclassified